An InDel in the Promoter of Al-ACTIVATED MALATE TRANSPORTER9 Selected during Tomato Domestication Determines Fruit Malate Contents and Aluminum Tolerance. Issue 9 (16th August 2017) - Ye, Jie; Wang, Xin; Hu, Tixu; Zhang, Fengxia; Wang, Bing; Li, Changxin; Yang, Tianxia; Li, Hanxia; Lu, Yongen; Giovannoni, James J.; Zhang, Yuyang; Ye, Zhibiao
Abstract : Sl- ALMT9, directly regulated by Sl- WRKY42, contributes to fruit malate accumulation both in fruit and root and enhances aluminum tolerance of tomato. Abstract: Deciphering the mechanism of malate accumulation in plants would contribute to a greater understanding of plant chemistry, which has implications for improving flavor quality in crop species and enhancing human health benefits. However, the regulation of malate metabolism is poorly understood in crops such as tomato ( Solanum lycopersicum ). Here, we integrated a metabolite-based genome-wide association study with linkage mapping and gene functional studies to characterize the genetics of malate accumulation in a global collection of tomato accessions with broad genetic diversity. We report that TFM6 (tomato fruit malate 6), which corresponds to Al-ACTIVATED MALATE TRANSPORTER9 (Sl -ALMT9 in tomato), is the major quantitative trait locus responsible for variation in fruit malate accumulation among tomato genotypes. A 3-bp indel in the promoter region of Sl -ALMT9 was linked to high fruit malate content. Further analysis indicated that this indel disrupts a W-box binding site in the Sl -ALMT9 promoter, which prevents binding of the WRKY transcription repressor Sl-WRKY42, thereby alleviating the repression of Sl -ALMT9 expression and promoting high fruit malate accumulation. Evolutionary analysis revealed that this highly expressed Sl -ALMT9 allele was selected for during tomato domestication. Furthermore, vacuole membrane-localized Sl-ALMT9 increases in abundance following Al treatment, thereby elevating malate transport and enhancing Al resistance.